Analysis of the Need for Android Based Mobile Learning Development to Improve Student Science Literations - Ulia Anisatur Rosidah; Putut Marwoto; Bambang Subali (Postgraduate, University of Mataram, 2021)
Science learning in Indonesia has not succeeded in increasing scientific literacy skills, as indicated by the decreasing international ranking from year to year. One of the efforts made to improve scientific literacy is using Android-based learning media. This study aims to analyze the need for the development of instructional media to improve students' scientific literacy at MTs Al Uswah Bergas Semarang Regency. This type of research is a descriptive study that is to describes the current situation. The data instruments used were interviews, observation, and questionnaires. The results of the research on the analysis of the needs for learning media based on android showed that 38% of the 80 students, namely 30 students agreed to develop Android-based learning media, while 29% of the students showed disagreement, 21% strongly agreed, and 12% strongly disagreed. There are aspects of literacy then students including; literacy as mastery of science as knowledge was 63%, 66% as a way of thinking, 62% of scientific literacy as a way of learning, 62% of the aspects of mastery of the competence of the interaction of science, technology, and society. Therefore, it is necessary to conduct research on the development of Android-based mobile learning media to improve students' scientific literacy